2013
DOI: 10.1002/chem.201300486
|View full text |Cite
|
Sign up to set email alerts
|

Pyracene‐Linked Bis‐Imidazolylidene Complexes of Palladium and Some Catalytic Benefits Produced by Bimetallic Catalysts

Abstract: Two new palladium complexes with a pyracene‐linked bis‐imidazolylidene (pyrabim) group have been obtained and fully characterized. The related monometallic analogues were obtained from the coordination of an acetanaphthene‐supported N‐heterocyclic carbene (NHC). The catalytic properties of all complexes were studied in the acylation of aryl halides with hydrocinnamaldehyde, and in the Suzuki–Miyaura coupling of aryl halides and aryl boronic acids. The results show that the presence of a second metal in the dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 53 publications
2
41
0
1
Order By: Relevance
“…(2), the reactions with 0.2 mol% of Pt/Nb 2 O 5 and Pt/HBEA for 52 h resulted in 76% and 90% yields, corresponding to TONs of 380 and 450, respectively. The TON by Pt/HBEA is 3~25 times larger than those by homogeneous [8][9][10][11][12][13][14][15] and heterogeneous 17 catalysts in the literature for the same reaction. ICP-AES analysis of the filtrate after the reaction with Pt/HBEA showed that the content of Pt in the solution was quite low (3.4 ppm).…”
mentioning
confidence: 68%
“…(2), the reactions with 0.2 mol% of Pt/Nb 2 O 5 and Pt/HBEA for 52 h resulted in 76% and 90% yields, corresponding to TONs of 380 and 450, respectively. The TON by Pt/HBEA is 3~25 times larger than those by homogeneous [8][9][10][11][12][13][14][15] and heterogeneous 17 catalysts in the literature for the same reaction. ICP-AES analysis of the filtrate after the reaction with Pt/HBEA showed that the content of Pt in the solution was quite low (3.4 ppm).…”
mentioning
confidence: 68%
“…Palladium complexes with a pyracene-linked bis-imidazolylidene group (C23, C24) and their monometallic counterparts (C25) have also been studied in the Suzuki coupling of aryl halides and aryl boronic acids. 63 The results showed that the presence of a second metal in dimetallic complexes induces some benefits in the catalytic behavior of the complexes (Table 4, entries 7 and 8). Kim et al prepared a series of ( π -allyl)Pd-NHC pseudohalogen complexes, [(π -allyl)Pd(X)(NHC)], and examined their catalytic activity in Suzuki-Miyaura cross-coupling reactions with arylboronic acids.…”
Section: 61mentioning
confidence: 98%
“…[6] Although these palladium-NHC complexes were generally effective in catalyzing the reaction with aryl iodides and bromides, general catalyst systems capable of utilizing a broad range of less reactive but inexpensive aryl chlorides remain elusive. [7] Their superior activity may be attributable to a higher local concentration of the metal in the dimetallic systems, or in some cases, to favorable supramolecular interactions between ligand and substrate. [6d] However, they were not efficient catalysts for aryl chloride substrates such as 4chlorobenzonitrile and 4-chlorobenzaldehyde, giving low yields in the range of 22-29%.…”
Section: Introductionmentioning
confidence: 99%